The Relationship Between COVID-19 and Male Hypogonadism in Denpasar, Bali, Indonesia - Joshua Limantoro; Eugenius Kurniawan Hane; Made Ratna Komala Cahyani; Stevanus Christian Surya; Gwyneth Felicia Oden; I Gusti Ngurah Pramesemara (Indonesian Andrology and Biomedical Journal, 2025)
Background : Hypogonadism in men can be identified through various clinical and subjective symptoms, which may be assessed using the Aging Male Symptoms (AMS) questionnaire. COVID-19 infection has been suggested to impact hormonal and reproductive function in men, but the relationship between post-infection symptoms and hypogonadism risk based on subjective measures remains underexplored in Indonesia. Objective : This study aims to determine the association between COVID-19-related characteristics and the risk of hypogonadism in men, assessed using the AMS score. Methods : A cross-sectional study was conducted on 152 male residents of Denpasar, Bali, aged ≥18 years. Data were collected through online and offline questionnaires, including demographics, lifestyle, COVID-19 infection history, and AMS scores. Bivariate and multivariate analyses were used to identify associations between COVID-19 indicators and hypogonadism risk. Results : Among respondents, 32.24% had an AMS score ≥27, indicating potential hypogonadism. A higher proportion of AMS ≥27 was found in individuals with obesity, comorbidities, occasional smoking, and moderate alcohol consumption. Although more severe COVID-19 indicators (e.g., hospitalization, prolonged symptoms, oxygen use) were observed in the AMS ≥27 group, statistical analysis showed no significant association between SARS-CoV-2 infection and hypogonadism risk (p > 0.05). Conclusion : While men with a history of COVID-19 infection exhibited higher AMS scores suggestive of hypogonadism, no statistically significant relationship was found. Further longitudinal studies with hormonal assays are needed to explore the long-term impact of COVID-19 on male reproductive health.